MEMAHAMI TOK WI PADA ALTAR SEMBAHYANGAN MASYARAKAT - Tulistyantoro, Lintu; Mariana, Mariana (Institute of Research and Community Outreach - Petra Christian University, 2006)
Tok wi is a cloth covering altar tables, playing an important role in a religious ritual of the Chinese society. Tok wi possesses a particular making pattern- following two space pattern, that is, the upper space and lower space with a one is to two composition. This cloth originates from China, made through the technique of weaving with silk as its main material. In a further development in Indonesia, it is made from mori cloth through the technique of batik.The changes in elements and colors used reflects vivid local influences. The tok wi pattern illustrates meaning according to the perspective of it user that possesses balance cosmology or harmonization between positive and the negative aspects to express the upper or spiritual world and the lower world.Currently, the understanding of this meaning seems to be unconsidered and many of its users only use it as a traditional criteria in their customs. Abstract in Bahasa Indonesia : Tok wi adalah kain penutup meja altar yang memiliki peran penting dalam satu ritual keagamaan mayarakat tionghoa. Tok wi memiliki aturan pola pembuatan yang tetap, yaitu mengikuti pola dua ruang yaitu ruang atas dan bawah dengan komposisi satu berbanding dua. Kain ini asalnya dari tionghoa dengan teknik pembuatan sulam dan berbahan dasar sutra. Perkembangannya di Indonesia kain ini terbuat dari kain mori dan dikerjakan dengan teknik batik. Perubahan ragam yang digunakan dan juga warna menunjukkan pengaruh lokal yang sangat tinggi. Pola Tok wi menggambarkan pemaknaan sesuai dengan cara pandang penggunanya yang memiliki kosmologi keseimbangan atau harmonisasi antara unsur positif dan unsur negatif untuk mengekspresikan dunia atas atau dunia roh (arwah) dan dunia bawah. Saat ini pemahaman akan makna tersebut tampaknya sudah mulai tidak dipahami, bahkan banyak diantara pemakai yang sekedar melengkapi sebagai persyaratan yang berlaku secara turun temurun. Kata kunci: Tok Wi, Batik, Tionghoa